2002
DOI: 10.1301/00296640260385919
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of the Thyroid-stimulating Hormone of the Anterior Pituitary Gland by Thyroid Hormone and by 9-Cis-Retinoic Acid

Abstract: Thyroid-stimulating hormone, TSH, of the anterior pituitary gland is regulated by the binding of the thyroid hormone-activated thyroid receptor to the TSH gene at the same time as the binding of the 9-cis-retinoic acid-activated retinoid X receptor to the same gene. Both interactions, separately or simultaneously, can suppress and thus regulate the expression of the TSH gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Synthesis and metabolism of thyroid hormones involve iodine, enzymes, and proteins and are also influenced by micronutrients and vitamins (9). VA takes part in the uptake of iodine while its deficiency impairs the synthesis of thyroglobulin and reduces the uptake of thyroidal iodine (31,32). Animals studies also found that thyroid of VA deficient rats took up less radioiodide than thyroid of control rats (32).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis and metabolism of thyroid hormones involve iodine, enzymes, and proteins and are also influenced by micronutrients and vitamins (9). VA takes part in the uptake of iodine while its deficiency impairs the synthesis of thyroglobulin and reduces the uptake of thyroidal iodine (31,32). Animals studies also found that thyroid of VA deficient rats took up less radioiodide than thyroid of control rats (32).…”
Section: Discussionmentioning
confidence: 99%
“…It can be suggested that after conversion to vitamin A, carotenoids influenced the production of thyroid gland hormones. There are some research showing that vitamin A level modulates thyroid gland metabolism [ 51 ] and that peripheral metabolism of thyroid hormone is necessary for the production of T4 [ 52 ] and of thyrotropin or TSH by pituitary [ 53 ]. It is known that thyroxin (T4) is a pro-hormone that must be converted to triiodothyronine, which takes place in the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal regulation of TH synthesis involves stimulation by thyrotropin releasing hormone (TRH) from the hypothalamus to synthesize TSH from the pituitary anterior pituitary gland (Wolf, 2002). TSH is regulated through TR homodimer of heterodimerization with 9- cis -retinoic acid-activated retinoid X receptor binding to the TSH gene, thereby regulating the expression of the TSH gene (Wolf, 2002).…”
Section: Hormonal Regulation Of Thyroid Hormone Secretionmentioning
confidence: 99%
“…TSH is regulated through TR homodimer of heterodimerization with 9- cis -retinoic acid-activated retinoid X receptor binding to the TSH gene, thereby regulating the expression of the TSH gene (Wolf, 2002). TSH stimulates thyroglobulin hydrolysis and increase of iodine metabolism leading to the secretion of THs from the thyroid gland (Yen, 2001).…”
Section: Hormonal Regulation Of Thyroid Hormone Secretionmentioning
confidence: 99%